Boron carbide-based bionic laminated ceramic material and preparation method thereof
Through bionic structure design and in-situ reaction sintering technology, a "A-B-A" type three-layer laminated ceramic structure was constructed, which solved the problems of strength, toughness and specific gravity of boron carbide ceramic materials in the prior art, and prepared boron carbide-based bionic laminated ceramic composite materials with high strength, high toughness and low specific gravity.
Patent Information
- Application Number
- CN202411679456.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
It is difficult to prepare boron carbide ultrafine grain ceramic materials with high strength, high toughness and low specific gravity, and the boron carbide content in boron carbide-titanium boronide composite ceramics has low material content, large material specific gravity, and reduced hardness.
The "A-B-A" type three-layer laminated ceramic structure is constructed through in-situ reaction sintering technology, using boron carbide, titanium carbide powder and boron powder as raw materials to regulate the content of boron carbide and achieve grain refinement and densification.
Boron carbide-based bionic laminated ceramic composite material with small specific gravity, good strength and toughness was prepared, with a volume density of 2.638g/cm3, a flexural strength of 826MPa, a hardness of 38.16GPa, and a fracture toughness of 7.93MPa·m1/2, significantly improving the comprehensive mechanical properties of the material.
Smart Images

Figure CN119528580A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lightweight ceramic material and an application field thereof, and more specifically to a boron carbide-based bionic laminated ceramic material and a preparation method thereof. Background Art
[0002] Boride ceramics are an important type of engineering material. Due to their unique physical and chemical properties (such as high hardness, high modulus, low specific gravity, excellent high temperature resistance and electrical conductivity), they have very important application prospects in modern high-tech industries. In the past decade, research on boride ceramic materials has attracted great attention at home and abroad. Under the premise of low specific gravity, how to further improve the mechanical properties of boron carbide ceramics is one of the key issues in current research. A large number of studies have shown that by refining the grain size of ceramic materials and preparing ultrafine-grained ceramics, the strength and toughness of the materials can be improved. At the same time, the second phase strengthening technology is also a technical approach to improve ceramic materials. However, the preparation of boron carbide nanopowder is very difficult, and rapid grain growth is inevitable during high-temperature sintering. Therefore, the preparation of ultrafine-grained boron carbide ceramics with high strength and high toughness is still a difficult problem. In recent years, scientists have studied the multi-level layered structure of the pearl layer of shells in nature, and developed the preparation and research of layered structure ceramics through bionic structure design. The design of layered ceramics is based on the mechanism of energy dissipation. Through reasonable stacking design, the sensitivity of the mechanical properties of the material to defects is reduced, thereby improving the toughness of the ceramics. Compared with bulk ceramics, cracks have a longer extension path in layered ceramics, thereby improving the fracture toughness. At the same time, due to the mismatch of the thermal expansion coefficients of each layer, the layered structure of the laminated ceramics will produce residual stress at the interface, and appropriate residual stress will also have a favorable effect on the mechanical properties. Therefore, the layered structure has a significant effect on improving the mechanical properties of ceramics. At present, studies have shown that the laminated structure can capture the main cracks and deflect the cracks. The fracture toughness of layered ceramics is significantly higher than that of bulk ceramics, and the layered ceramics are less sensitive to defects and damage. The laminated structure has broad research potential for improving the mechanical properties of boron carbide-based ceramics. In terms of dispersion strengthening and toughening technology, it is found that among various boron carbide ceramic reinforcement phase candidate materials, titanium boride is the most promising reinforcement phase. It has high hardness, high modulus, and low specific gravity. It is an ideal reinforcement for boron carbide lightweight ceramic composites.
[0003] The densification of boron carbide ceramics is very difficult. Generally, ceramic micropowders are mixed and then sintered at high temperature and pressure. The sintering temperature is high, and the material microstructure and performance are not ideal. Studies have shown that the in-situ reaction synthesis preparation method can not only obtain ultra-fine grain structure of boron carbide composite ceramics, but also achieve uniform composite material organization and grain refinement, and is expected to obtain excellent performance.
[0004] In-situ synthesis reactions generally use chemical reactions to achieve material synthesis. Related studies have shown that in the in-situ synthesis system of boron carbide-titanium boride composite ceramics, the chemical reaction between titanium carbide and boron can be used to obtain boron carbide-titanium boride composite ceramics. However, in this synthesis system, the composition ratio between boron carbide-titanium boride composite ceramics is generally determined according to the chemical reaction equation, which is difficult to control within a large range. The content of boron carbide is generally not more than 45wt%, which leads to a significant increase in the specific gravity of the boron carbide composite ceramics, the loss of the characteristics of light-weight boron carbide ceramics, and a decrease in its hardness. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a boron carbide-based bionic laminated ceramic material and a preparation method thereof, which has a simple process, good bonding between the layers, can well control the microstructure and interface structure, achieve grain refinement, and prepare a boron carbide-based bionic laminated ceramic composite material with low specific gravity, good strength and toughness.
[0006] The technical solution adopted by the present invention to solve the technical problem is: constructing a preparation method of a boron carbide-based bionic laminated ceramic material, comprising the following steps:
[0007] S1. Boron carbide powder, titanium carbide powder and boron powder are mixed with anhydrous ethanol as a medium. The mixed slurry is subjected to rotary evaporation, dried in a vacuum drying oven, and then sieved and granulated to obtain A and B ternary mixed powders;
[0008] S2. The A and B ternary mixed powders are laid flatly into a graphite mold in sequence to form an "ABA" type three-layer structure, and high-temperature pressure sintering is performed under vacuum conditions to prepare a boron carbide-based bionic laminated ceramic material.
[0009] According to the above scheme, the particle size of the boron carbide powder is 2-8μm, and the purity is greater than 97%; the particle size of the titanium carbide powder is 2-4μm, and the purity is greater than 99%; the particle size of the boron powder is 1-3μm, and the purity is greater than 95%; the raw powder mixture of the boron carbide powder, titanium carbide powder and boron powder includes 55.14wt%-82.03wt% of boron carbide powder, 8.60wt%-21.56wt% of titanium carbide powder, and 9.36wt%-23.30wt% of boron powder by weight percentage.
[0010] According to the above scheme, in the "ABA" type three-layer structure, the thickness of the outer layer after sintering and processing is about 0.75 mm, and the thickness of the middle layer is 1.5 mm.
[0011] According to the above scheme, in step S1, the boron carbide powder, titanium carbide powder and boron powder are milled in a planetary ball mill at a speed of 200-300 r / min.
[0012] According to the above scheme, in step S1, the temperature of the vacuum drying oven is 60-100° C., and the drying time is 24-48 hours.
[0013] According to the above scheme, in step S1, the sieving is 100-325 mesh.
[0014] According to the above scheme, in step S2, the vacuum condition is better than 20Pa.
[0015] According to the above scheme, in step S2, the method of high temperature pressure sintering is: heating to 1400°C at a heating rate of 10-15°C / min under a pressure of 10MPa, then heating to 1950-2000°C at a heating rate of 10-15°C / min, and at the same time increasing the pressure to 30MPa. Sintering is carried out at a temperature and pressure of 30-60min, and then naturally cooled.
[0016] The invention also provides a boron carbide-based bionic laminated ceramic material, which is made by the preparation method of the boron carbide-based bionic laminated ceramic material.
[0017] According to the above scheme, the volume density of the prepared boron carbide-based laminated ceramic is 2.638 g / cm 3 , flexural strength is 826MPa, hardness is 38.43GPa, fracture toughness is 7.93MPa·m 1 / 2 .
[0018] The boron carbide-based bionic laminated ceramic material and the preparation method thereof of the present invention have the following beneficial effects:
[0019] 1. The present invention adopts in-situ reaction sintering technology to prepare boron carbide-titanium boride composite materials with boron carbide, titanium carbide powder and boron powder as raw materials, which solves the problems of low boron carbide content, high material specific gravity, decreased hardness and the key preparation technology of the difficulty in uniform mixing and dispersion of ultrafine powders in in-situ composite boron carbide ceramics. The sintered composite ceramics have the advantages of fine grains and high density.
[0020] 2. The present invention has designed a bionic "ABA" type three-layer laminated ceramic structure. Each layer has good interface bonding, which provides an additional strengthening mechanism for boron carbide ceramics. While maintaining the low density of boron carbide-based ceramics, the bending strength, hardness and fracture toughness increase synergistically, and excellent comprehensive mechanical properties are obtained. The volume density under the optimal process conditions is 2.638g / cm 3 , flexural strength is 826MPa, hardness is 38.16GPa, fracture toughness is 7.93MPa·m 1 / 2 .
[0021] 3. The present invention adopts the principle of in-situ synthesis technology and develops a three-layer laminated composite ceramic material of boron carbide-titanium boride through bionic structure design to improve the comprehensive performance and application range of boron carbide ceramics. The research results have important application value in the fields of wear-resistant ceramic parts and impact-resistant protective materials. The raw materials used are easy to obtain, the preparation process is simple, the preparation cost is low, the product is easy to process, and it is suitable for large-scale production;
[0022] 4. The present invention makes full use of the energy and highly active products released by the in-situ synthesis reaction between titanium carbide and elemental boron to promote densification and refine the grain size; at the same time, it adopts a bionic laminated structure design to provide an additional strengthening mechanism for ceramics, solves the problem that the bending strength, hardness and fracture toughness of boron carbide-based ceramics cannot grow synergistically, and further improves the mechanical properties of boron carbide ceramics. The resulting product has the characteristics of low density, high strength, high hardness, etc.
[0023] 5. In order to control the content of boron carbide within a larger range and meet the needs of interlayer bonding of laminated ceramics, the present invention, based on fully utilizing the advantages of in-situ synthesis of boron-titanium carbide, adds ultrafine boron carbide raw materials to the synthesis system to control the content of boron carbide, thereby achieving arbitrary control of the boron carbide content between 75-90wt%. Under the premise of ensuring the high hardness and low specific gravity of the boron carbide composite ceramic material, the mechanical properties of the material are improved and the sintering preparation temperature is reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described below with reference to the accompanying drawings and embodiments, in which:
[0025] Figure 1 Schematic diagram of the boron carbide-based bionic laminated ceramic structure in Examples 1 and 2 of the present invention;
[0026] Figure 2 This is a cross-sectional SEM image of the boron carbide-based bionic laminated ceramic in Example 1 of the present invention;
[0027] Figure 3 is the XRD diagram of the boron carbide-based bionic laminated ceramic in Example 1 of the present invention;
[0028] Figure 4 is the XRD diagram of the boron carbide-based bionic laminated ceramic in Example 2 of the present invention;
[0029] Figure 5 is the XRD diagram of the boron carbide-based single-layer ceramic in the comparative example of the present invention;
[0030] Figure 6 This is a cross-sectional SEM image of the first layer of the boron carbide-based bionic laminated ceramic in Example 1 of the present invention;
[0031] Figure 7This is a cross-sectional SEM image of the second layer of the boron carbide-based bionic laminated ceramic in Example 1 of the present invention;
[0032] Figure 8 This is a cross-sectional SEM image of the third layer of the boron carbide-based bionic laminated ceramic in Example 1 of the present invention;
[0033] Fig. 9 This is a cross-sectional SEM image of the first layer of the boron carbide-based bionic laminated ceramic after etching in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described in detail with reference to the accompanying drawings.
[0035] Example 1
[0036] A method for preparing a boron carbide-based bionic laminated ceramic comprises the following steps:
[0037] Step 1, weighing 82.03wt% of boron carbide powder, 8.60wt% of titanium carbide powder and 9.37wt% of boron powder as mixture A; weighing 73.07wt% of boron carbide powder with an average particle size of 2μm, 12.90wt% of titanium carbide powder and 14.03wt% of boron powder as mixture B. Mixture A and mixture B are respectively mixed with anhydrous ethanol as a medium, using a planetary ball mill at a speed of 250r / min for 2h, and then rotary evaporated to obtain mixed slurries A and B. Mixed slurries A and B are dried in a vacuum drying oven at 60°C for 24h, then ground, and granulated through a 200-mesh sieve to obtain raw powder mixtures A and B.
[0038] Step 2: Lay the raw powder mixtures A and B in the following order into a graphite mold: the first layer is powder A, the second layer is powder B, and the third layer is powder A. Then place it in a vacuum pressure sintering furnace for vacuum sintering, and keep the vacuum better than 20Pa. Heat it up to 1400℃ at a heating rate of 10℃ / min under a pressure of 10MPa, and then heat it up to a maximum temperature of 1950-2000℃ at a heating rate of 10℃ / min, and the pressure is raised to 30MPa. Sinter it for 30 minutes under heat and pressure, and then cool it naturally to obtain a dense boron carbide-based laminated ceramic material.
[0039] The XRD test results are as follows Figure 3 As shown in the figure, the results show that there are only two phases of B4C and TiB2 in the product, indicating that the raw materials TiC and B react completely during the sintering process to generate B4C and TiB2, and no other impurities exist. This proves that the reaction sintering method adopted by the present invention is feasible and can obtain the sintered material with the expected composition. The SEM results are shown in Figure 2 ,6 As shown in Figures 7 and 8, the results show that the laminated material has good interface bonding and clear interface structure, the white TiB2 is evenly distributed in the black B4C matrix, the grain size of TiB2 is about 2-4μm, and the grain size of B4C is about 1-3μm. The volume density of the boron carbide-based laminated ceramic prepared in this embodiment 1 is 2.638g / cm 3 , flexural strength is 826MPa, hardness is 38.16GPa, fracture toughness is 7.93MPa·m 1 / 2 .
[0040] Example 2
[0041] A method for preparing a boron carbide-based bionic laminated ceramic comprises the following steps:
[0042] Step 1, weighing 73.07wt% of boron carbide powder, 12.90wt% of titanium carbide powder and 14.03wt% of boron powder as mixture A; weighing 64.11wt% of boron carbide powder with an average particle size of 2μm, 17.22wt% of titanium carbide powder and 18.67wt% of boron powder as mixture B. Mixture A and mixture B are respectively mixed with anhydrous ethanol as a medium, using a planetary ball mill at a speed of 250r / min for 2h, and then rotary evaporated to obtain mixed slurries A and B. Mixed slurries A and B are dried in a vacuum drying oven at 60°C for 24h, then ground, and granulated through a 200-mesh sieve to obtain raw powder mixtures A and B.
[0043] Step 2: Lay the raw powder mixtures A and B in the following order into a graphite mold: the first layer is powder A, the second layer is powder B, and the third layer is powder A. Then place it in a vacuum pressure sintering furnace for vacuum sintering, and keep the vacuum better than 20Pa. Heat it up to 1400℃ at a heating rate of 10℃ / min under a pressure of 10MPa, and then heat it up to a maximum temperature of 1950-2000℃ at a heating rate of 10℃ / min, and the pressure is raised to 30MPa. Sinter it for 30 minutes under heat and pressure, and then cool it naturally to obtain a dense boron carbide-based laminated ceramic material.
[0044] The XRD test results are as follows Figure 4 The results show that there are only two phases of B4C and TiB2 in the product. The volume density of the boron carbide-based laminated ceramic prepared in this embodiment 2 is: 2.713 g / cm 3 , flexural strength 753.5MPa, hardness 37.92GPa, fracture toughness 8.11MPa·m 1 / 2 .
[0045] Comparative Example
[0046] A method for preparing a boron carbide-based single-layer ceramic comprises the following steps:
[0047] Step 1: Weigh 82.03wt% of boron carbide powder, 8.60wt% of titanium carbide powder and 9.37wt% of boron powder as a mixture, use anhydrous ethanol as a medium, use a planetary ball mill, mix for 2h at a speed of 250r / min, and then rotary evaporate to obtain a mixed slurry. Dry the mixed slurry in a vacuum drying oven at 60°C for 24h, then grind it, and granulate it through a 200-mesh sieve to obtain a raw material powder mixture.
[0048] Step 2: Place the raw powder mixture into a graphite mold, and then place it in a vacuum pressure sintering furnace for vacuum sintering. Keep the vacuum better than 20Pa, and heat it to 1400℃ at a heating rate of 10℃ / min under a pressure of 10MPa, and then heat it to a maximum temperature of 1950℃ at a heating rate of 10℃ / min, and at the same time, the pressure is increased to 30MPa. Sintering is carried out for 30 minutes under heat and pressure, and then naturally cooled to obtain a dense boron carbide-based laminated ceramic material.
[0049] The XRD test results are as follows Figure 5 As shown, the results show that there are only two phases of B4C and TiB2 in the product. The properties of the prepared boron carbide-based composite ceramics are as follows: volume density 2.706g / cm 3 , flexural strength 741.8MPa, hardness 34.63GPa, fracture toughness 6.05MPa·m 1 / 2 .
[0050] Table 1 Density and mechanical properties of ceramics in Examples 1, 2 and Comparative Examples
[0051]
[0052] In summary, it can be understood that the boron carbide-based laminated ceramics prepared by bionic structure design have a clear interface structure and good interface bonding, presenting an "ABA" type three-layer structure. In addition, by adopting in-situ reaction sintering technology, TiB2 in the laminated ceramics is evenly distributed in the B4C matrix, the grains in the material are very tightly bonded and the grains are relatively small. Compared with the single-layer ceramics in the comparative example, the bending strength of the laminated ceramics in Example 1 is increased from 741.8MPa to 826MPa, the hardness is increased from 34.63GPa to 38.16GPa, and the fracture toughness is increased from 6.05MPa·m1 / 2 to 7.93MPa·m1 / 2. Compared with the single-layer ceramics in the comparative example, the laminated structure significantly improves the bending strength, hardness and fracture toughness, while maintaining a low density. The present invention provides a new method for preparing boron carbide-based ceramics with high strength and high toughness, and the prepared boron carbide-based laminated ceramic composite material is expected to be used in the fields of wear-resistant ceramic parts, impact-resistant protective materials, etc.
[0053] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for preparing a boron carbide-based bionic laminated ceramic material, characterized in that: The following steps are involved: S1. Boron carbide powder, titanium carbide powder and boron powder are mixed with anhydrous ethanol as a medium. The mixed slurry is subjected to rotary evaporation, dried in a vacuum drying oven, and then sieved and granulated to obtain A and B ternary mixed powders; S2. The A and B ternary mixed powders are laid flatly into a graphite mold in sequence to form an "ABA" type three-layer structure, and high-temperature pressure sintering is performed under vacuum conditions to prepare a boron carbide-based bionic laminated ceramic material.
2. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 1, characterized in that: The boron carbide powder has a particle size of 2-8 μm and a purity greater than 97%; the titanium carbide powder has a particle size of 2-4 μm and a purity greater than 99%; the boron powder has a particle size of 1-3 μm and a purity greater than 95%; the raw powder mixture of the boron carbide powder, titanium carbide powder and boron powder comprises, by weight percentage, 55.14wt%-82.03wt% of boron carbide powder, 8.60wt%-21.56wt% of titanium carbide powder and 9.36wt%-23.30wt% of boron powder.
3. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 1, characterized in that: In the "ABA" type three-layer structure, the thickness of the outer layer after sintering and processing is about 0.75 mm, and the thickness of the middle layer is 1.5 mm.
4. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 2, characterized in that: In the step S1, boron carbide powder, titanium carbide powder and boron powder are mixed by a planetary ball mill, and the rotation speed of the planetary ball mill is 200-300 r / min.
5. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 3, characterized in that: In step S1, the temperature of the vacuum drying oven is 60-100° C., and the drying time is 24-48 hours.
6. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 4, characterized in that: In the step S1, the sieving is 100-325 mesh.
7. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 1, characterized in that: In step S2, the vacuum condition is better than 20Pa.
8. The method for preparing the boron carbide-based bionic laminated ceramic material according to claim 7, characterized in that: In step S2, the method of high temperature pressure sintering is: heating to 1400°C at a heating rate of 10-15°C / min under a pressure of 10MPa, then heating to 1950-2000°C at a heating rate of 10-15°C / min, while the pressure is increased to 30MPa; sintering at a temperature of 30-60min, and then cooling naturally.
9. A boron carbide-based bionic laminated ceramic material, characterized in that: The material is made by the preparation method of the boron carbide-based bionic laminated ceramic material according to any one of claims 1 to 8.
10. A boron carbide-based bionic laminated ceramic material according to claim 9, characterized in that: The volume density of the prepared boron carbide-based laminated ceramics is 2.638 g / cm 3 , flexural strength is 826MPa, hardness is 38.43GPa, fracture toughness is 7.93MPa·m 1 / 2 .
Citation Information
Patent Citations
Compound for anode material of lithium ion secondary battery and preparation method thereof
CN101728513A
Early-strength, low-shrinkage and high-toughness cement-based engineering material and preparation method thereof
CN105948665A
Multifunctional boron carbide-based multiphase ceramic, and reactive hot-pressing sintering preparation method thereof
CN110128146A
Boron carbide-based composite ceramic material and preparation process thereof
CN110256081A
Method for sintering boron carbide-titanium boride material through spark plasma reaction
CN111116202A